Anarchisme et sexualité en Espagne jusqu’en 1939 - Jean-Louis Guereña (Cahiers de Civilisation Espagnole Contemporaine)
This contribution examines the space occupied by the sexuality within the « anarchist Spanish culture », by approaching diverse points which show the presence and the importance of a real « sexual culture » in the anarchistic sphere of influence: the sex education and the disclosure of the sexuality, the eugenics, the neoMalthusianism and the control of the birth rate, fights against the prostitution regulated and the « venereal diseases », as said then, and finally the homosexuality.